Tips and tricks: artistic effects for images in PowerPoint / Rafizah Kechil, Wan Anisha Wan Mohammad and Azlina Mohd Mydin - Kechil, Rafizah; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina (Unit Penerbitan dan Publisiti JSKM, 2022)
The purpose of this tip is to share how to use artistic effects for images in PowerPoint. It is hoped that by sharing this tip, we will be able to handle our daily tasks more creatively using existing software. In PowerPoint, click on an image and then choose "Picture Format" to apply artistic effects to it. Then, select "Artistic Effects". Choose a creative effect that is appropriate for our needs.